2023
DOI: 10.3389/fpubh.2023.1054559
|View full text |Cite
|
Sign up to set email alerts
|

Online HIV prophylaxis delivery: Protocol for the ePrEP Kenya pilot study

Abstract: BackgroundOnline pharmacies in Kenya provide sexual and reproductive health products (e.g., HIV self-testing, contraception) and could be leveraged to increase the reach of HIV pre-exposure and post-exposure prophylaxis (PrEP/PEP) to populations who do not frequently attend health facilities. To date, evidence is limited for operationalizing online PrEP/PEP delivery and the type of populations reached with this differential service delivery model.MethodsThe ePrEP Kenya Pilot will deliver daily oral PrEP and PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous research has demonstrated the usefulness of digital interventions in addressing various health challenges such as HIV/STIs [ 57 59 ], mental health [ 60 ] and substance use [ 61 ] among YMSM, as well as accessing social support in coming out and finding a community to belong to [ 62 ]. An ongoing study in Kenya is assessing acceptability, feasibility and cost implications of online PrEP and PEP delivery among a diverse clientele within the Nairobi metropolis [ 63 ]. We suggest that digital interventions should be considered for service delivery among YMSM in Kenya, given the demonstrated potential usefulness of such interventions [ 64 ], and the ubiquitous use of smart phones in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the usefulness of digital interventions in addressing various health challenges such as HIV/STIs [ 57 59 ], mental health [ 60 ] and substance use [ 61 ] among YMSM, as well as accessing social support in coming out and finding a community to belong to [ 62 ]. An ongoing study in Kenya is assessing acceptability, feasibility and cost implications of online PrEP and PEP delivery among a diverse clientele within the Nairobi metropolis [ 63 ]. We suggest that digital interventions should be considered for service delivery among YMSM in Kenya, given the demonstrated potential usefulness of such interventions [ 64 ], and the ubiquitous use of smart phones in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although innovative approaches to the community delivery of self-testing kits for HIV and ART, oral PrEP, and PEP have been and are being studied, [10][11][12][13][14] the unrestricted access that we propose has not, to our knowledge, been implemented in any region of east, central, southern, and west Africa. Pilot implementation studies with process evaluation would be needed before a full implementation is made, to enable an understanding of the contexts in which community TLD is adopted as local policy, made available widely and discreetly, and used by community members.…”
Section: Introductionmentioning
confidence: 99%
“…HIVST may help overcome some of these challenges by enabling community-based PrEP delivery models outside clinic settings (e.g. online delivery [13] and pharmacy delivery [14]) and increasing efficiencies within clinic-based PrEP delivery models (e.g. testing while waiting [15] and multi-month dispensing supported with interim HIVST [16]).…”
Section: Introductionmentioning
confidence: 99%